2006
DOI: 10.1124/mol.106.025817
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Hypoxia-Inducible Factor-1 by Degrading Aryl Hydrocarbon Receptor Nuclear Translocator: A Mechanism of Tumor Growth Inhibition

Abstract: Hypoxia-inducible factor-1 (HIF-1), a transcription factor composed of HIF-1␣ and aryl hydrocarbon receptor nuclear translocator (ARNT), plays a key role in cell survival and angiogenesis in hypoxic tumors, and many efforts have been made to develop anticancer agents that target HIF-1␣. However, although ARNT is also required for HIF-1 activity, ARNT has been disregarded as a therapeutic target. Curcumin is a commonly used spice and coloring agent with a variety of beneficial biological effects, which include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
112
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(129 citation statements)
references
References 34 publications
11
112
1
5
Order By: Relevance
“…In contrast, ARNT mRNA was not affected by these treatments (Choi et al, 2006), indicating the possibility of post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, ARNT mRNA was not affected by these treatments (Choi et al, 2006), indicating the possibility of post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that the ARNT protein level was decreased by H 2 O 2 or ROS in human cell lines (Choi et al, 2006(Choi et al, , 2008. In contrast, ARNT mRNA was not affected by these treatments (Choi et al, 2006), indicating the possibility of post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies, also, report that it is an agent possessing a wide variety of biological and pharmacological activities, including anti-proliferation (Choi et al, 2006), antiapoptosis (Aggarwal et al, 2008), anti-angiogenesis (Lin et al, 2007) and inhibition of cell invasion and metastasis (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, EF24 is not only significantly more active than curcumin, but it also inhibits HIF-1 via a totally distinct mechanism. We found that curcumin inhibited HIF-1α transcription only at the highest concentration examined (50-100 μM), whereas EF24 downregulated HIF-1α in a dose-dependent manner at low, sublethal concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…12 In this study, we set out to elucidate aspects of the molecular mechanism of action of EF24. We focused on the reported antiangiogenic activities of curcumin, partially mediated by inhibition of the hypoxia-inducible factor (HIF-1) pathway 13,14 and determined whether EF24 had an effect on the HIF pathway.…”
Section: Introductionmentioning
confidence: 99%